Optimization of People's Palm Oil Replanting (PSR) in a Sustainable Manner in Indragiri Hilir Regency: Optimalisasi Peremajaan Sawit Rakyat (PSR) secara Berkelanjutan di Kabupaten Indragiri Hilir - Adisti, Suci; Nasution, Mimin Sundari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the optimization of PSR in a sustainable manner in Indragiri Hilir Regency and identify the inhibiting factors. Using a descriptive qualitative method with a case study approach, this research found that the optimization of PSR in Indragiri Hilir Regency has not been optimal. The goal indicators have not yet been achieved, although initial successes can be seen from physical changes in the plantation, increased farmer participation, and the area of rejuvenated land. Although various alternatives have also been carried out, there are still constraints on limiting resources, such as limited post-planting funds and PSR assistants, obstacles related to legality, lack of cooperation with partners, and technical assistance in the field. For this reason, researchers recommend the addition of assistants, accelerating the completion of land legality, and increasing cooperation with partners. In addition, future research can examine more effective partnership models, the social impact of PSR, and the optimization of PSR on peatlands.